KONSTRUKSI PIMPINAN TERHADAP PERAN DAN FUNGSI PUBLIC RELATIONS DI INDONESIA (UNIVERSITAS BRAWIJAYA DAN UNIVERSITAS HASANUDDIN) - Putra, Mohammad Annur Tri; Kriyantono, Rachmat; Wulandari, Maulina Pia (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2019)
This study aims to explain how leaders construct opinions about the function of public relations (PR) in Indonesian universities (Universitas Brawijaya and Hasanuddin University). This research is qualitative research using the construction paradigm and phenomenology approach. The results of the study indicate that the construction of leadership roles and functions of public relations in these two universities has similarities and there are also differences in perspectives due to circumstances. The construction of leadership occurs according to the conditions on campus.